Faktor yang Mempengaruhi Keputusan Pembelian Produk Sanken melalui Aplikasi Mobile Shopee - Anung Widodo; Arief Budi Ibrahim (EBISMAN eBisnis Manajemen, 2025)
This study aims to analyze the influence of Brand awareness, price and Viral marketing variables on Sanken product decisions. This research method is quantitative. The population used in this study was 80 respondents with accidental and interview methods. The partial influence of the Brand awareness variable (X1) has an influence on purchasing decisions of 93.3%, while the influence of the price variable (X2) has an influence on the Purchase decision variable of 7.4%, and the influence of Viral marketing (X3) on Purchase decisions of 66.2%, The influence of the Brand awareness variable (X1), Price (X2) and Viral marketing (X3) simultaneously on the Purchase decision variable is 94.7%, while the remaining 5.3% is determined by other unknown factors that are not included in the research model.